Carbonyls: Powerful Organic Materials for Secondary Batteries. Issue 11 (8th April 2015) - Häupler, Bernhard; Wild, Andreas; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> The application of organic carbonyl compounds as high performance electrode materials in secondary batteries enables access to metal‐free, low‐cost, environmental friendly, flexible, and functional rechargeable energy storage systems. Organic compounds have so far not received much attention as potential active materials in batteries, mainly because of the success of inorganic materials in both research and commercial applications. However, new requirements in secondary batteries such as flexibility accompanied with low production costs and environmental friendliness, in particular for portable devices, reach the limit of inorganic electrode materials. Organic carbonyl compounds represent the most promising materials to satisfy these needs. Here, recent efforts of the research in the field of organic carbonyl materials for secondary batteries are summarized, and the working principle and the structural design of different groups of carbonyl material is presented. Finally, the influence of conductive additives and binders on the cell performance is closely evaluated for each class of materials.